The French press in the Age of Enlightenment - Censer, Jack Richard (Routledge, 1994)
Jack Censer's achievement in this volume is to marshal a vast literature in order to provide a coherent and original interpretation of the role of the French press in the dissemimation of social and political ideas in the pre-Revolution years.